Using the Caprini Risk Score to Increase VTE Awareness in the Community: The Know Your Score Project. (July 2022) - Saadaldin, Hassan; Shetye, Prasad; Gavankar, Sanket; Laddu, Atul R.; Tafur, Alfonso; Caprini, Joseph A.
Abstract presented during the ISTH congress 2021 Shetye, P., Gavankar, S, Saadaldin, H, et al, Using the Caprini Risk Score to Increase VTE Awareness in the Community. The Know Your Score Project. AS-ISTH-2021-02054, 2021